Intake of Cruciferous Vegetables Modifies Bladder Cancer Survival - Tang, Li (2010)
BACKGROUND: Intake of cruciferous vegetables, a rich source of dietary isothiocyanates, has been inversely associated with risk of bladder cancer. Due to the potent antiproliferative effects of dietary isothiocyanates on bladder cancer in both in vitro and in vivo models, cruciferous vegetable intake may also play a role in survival among patients with bladder cancer. METHODS: Utilizing information obtained from the Roswell Park Cancer Institute Tumor Registry, patient medical records, and routinely-collected questionnaire data, we examined potential associations between intake of cruciferous vegetables and survival among bladder cancer patients. As cooking can substantially reduce or destroy isothiocyanates, consumption of raw versus cooked cruciferous vegetables was examined separately. Hazard ratios (HR) and 95% confidence intervals (CI) were estimated using Cox proportional hazard models. RESULTS: A total of 239 bladder cancer patients were included in the study. After an average of 8 years of follow-up, 179 deaths occurred, with 101 deaths attributable to bladder cancer. After adjustment for other prognostic factors, a strong and significant inverse association was observed between bladder cancer mortality and broccoli intake, in particular raw broccoli intake (≥ 1 versus < 1 serving per month; HR for overall death, 0.57; 95% CI, 0.39–0.83; HR for disease-specific death, 0.43; 95% CI, 0.25–0.74). There were no significant associations for total vegetables, total fruits, or other individual cruciferous vegetables. CONCLUSIONS: Considering the strong preclinical evidence, intake of broccoli may improve bladder cancer survival. IMPACT: Further prospective investigation is warranted to confirm the potential role of cruciferous vegetables in bladder cancer prognosis.